Human citrate synthase kinetic simulation to fit rapid, direct, and thiol probe coupled kinetic data - Noah Shackelford; Zach Zavodny; Samantha Schindler; Nathan Fancher; Allen A. Thomas; Michael A. Moxley (Biochemistry and Biophysics Reports)
Human citrate synthase (hCS) was kinetically characterized through full progress curve kinetic modelling using kinetic simulation, global fitting of the direct AcCoA to CoA transition, and a coupled thiol probe reaction to better determine the kinetics with low substrate concentration. Our analysis provides one of the most rigorous kinetic analyses of any citrate synthase ruling out the need to invoke complex cooperative mechanisms to explain progress curve data. Furthermore, we collected and modeled stopped-flow pH-dependent kinetic data with CoA and popular thiol probes such as Ellman's reagent (DTNB) and 4,4′-Dithiodipyridine (DPS), providing the opportunity for detailed kinetic simulations using these thiol probes with CoA producing enzymes. Global fitting suggests that the DPS/CoA bimolecular rate constant increased 100-fold via protonation of the pyridine ring (pKa = 5.2), quantifying its kinetic advantage relative to DTNB. To explore the kinetic effects of polar substituents on the pyridine ring, we synthesized three different DPS analogs by adding either an alcohol, amine, or carboxylic acid moiety to the pyridine ring. Of these, the alcohol group provided the most similar kinetic characteristics to DPS but greatly increases thiol probe polarity offering an alternative to DPS.